Variations in influenza vaccination coverage among the high-risk population in Sweden in 2003/4 and 2004/5: a population survey - van Essen Gerrit A; Kroneman Madelon W (BMC, 2007)
Abstract Background In Sweden, the vaccination campaign is the individual responsibility of the counties, which results in different arrangements. The aim of this study was to find out whether influenza vaccination coverage rates (VCRs) had increased between 2003/4 and 2004/5 among population at high risk and to find out the influence of personal preferences, demographic characteristics and health care system characteristics on VCRs. Methods An average sample of 2500 persons was interviewed each season (2003/4 and 2004/5). The respondents were asked whether they had had an influenza vaccination, whether they suffered from chronic conditions and the reasons of non-vaccination. For every county the relevant health care system characteristics were collected via a questionnaire sent to the medical officers of communicable diseases. Results No difference in VCR was found between the two seasons. Personal invitations strongly increased the chance of having had a vaccination. For the elderly, the number of different health care professionals in a region involved in administering vaccines decreased this chance. Conclusion Sweden remained below the WHO-recommendations for population at high risk due to disease. To meet the 2010 WHO-recommendation further action may be necessary to increase vaccine uptake. Increasing the number of personal invitations and restricting the number of different administrators responsible for vaccination may be effective in increasing VCRs among the elderly.